2018
DOI: 10.1186/s13020-018-0174-0
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis therapy by Chinese medicine and modern agents

Abstract: Psoriasis is a chronic, painful, disfiguring and non-contagious skin disease that has globally affected at least 200 million patients. In general, mild to moderate psoriasis patients will be treated by chemical drugs or Chinese medicine, while targeting systemic biological drugs have been successfully developed with good efficacy but high cost burden to patients with severe psoriasis. Since the underlying mechanisms of psoriasis are not well understood, in this review, psoriasis pathogenesis and clinical thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 38 publications
0
42
0
3
Order By: Relevance
“…In addition, the cost of biologics is high. It would therefore be desirable to use botanical products as alternative psoriasis treatments that are inexpensive and have fewer side effects . A large number of botanicals have been studied for the treatment of psoriasis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the cost of biologics is high. It would therefore be desirable to use botanical products as alternative psoriasis treatments that are inexpensive and have fewer side effects . A large number of botanicals have been studied for the treatment of psoriasis .…”
Section: Discussionmentioning
confidence: 99%
“…It would therefore be desirable to use botanical products as alternative psoriasis treatments that are inexpensive and have fewer side effects. 36 A large number of botanicals have been studied for the treatment of psoriasis. 24,37 The research on molecular targets and mechanisms of natural products has greatly contributed to the progress in the treatment of skin diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The main characteristics of psoriasis are excessive proliferation of keratinocytes and being easy to relapse; however, it was reported that the disease can affect many tissues in the muscles, joints, digestive tract and even eyes. Therefore, it is agreed that PS is one of the forms of psoriatic disease (PD) (Ritchlin, 2007;Meng et al, 2018). Psoriasis possesses a major social and economic burden on society as the existent therapies only relieve symptoms and cannot cure disease.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, qi and blood coagulated and blocked the meridians, which led to lack of nourishment for the skin and muscle. Thus, TCM clinical experts advocated 'treatment of psoriasis from the blood aspect' [11,12]. The effective ways to achieve this are blood-activating herbal medicines and treatments such as acupuncture and bloodletting.…”
Section: Introductionmentioning
confidence: 99%